Are professional footballers becoming lighter and more ectomorphic? Implications for talent identification and development - Nevill, A. M.; Okojie, D. I.; Smith, J.; O'Donoghue, P. G.; Webb, T. (International Journal of Sports Science & Coaching, 2019)
The identification and development of talent is an essential component of modern professional football. The recognition of key physical characteristics of such footballers who successfully progress through talent development programs is of considerable interest to academics and those working in professional football. Using Football Yearbooks, we obtained the height, body mass and ages of all players from the English top-division over the seasons 1973-4, 1983-4, 1993-4, 2003-4 and 2013-4, calculating body-mass index (BMI) (kg/m2) and reciprocal ponderal index (RPI) (cm/kg0.333). The mean squad size increased over these decades from n = 22.4 (1973-4) to n = 27.8 (2013-4). Height also increased linearly by approximately 1.2 cm per decade. Body mass increased in the first four decades, but declined in the final season (2013-4). Regression analysis confirmed inverted "u" shape trends in both body mass and BMI, but a "J" shape trend in RPI, indicating that English top-division professional footballers are getting more angular and ectomorphic. We speculate that this recent decline in BMI and rise in RPI is due to improved quality of pitches and increased work-load required by modern-day players. Defenders were also found to be significantly taller, heavier, older and, assuming BMI is positively associated with lean mass, more muscular than other midfielders or attackers. The only characteristic that consistently differentiated successful with less successful players/teams was age (being younger). Therefore, English professional clubs might be advised to attract young, less muscular, more angular/ectomorphic players as part of their talent identification and development programs to improve their chances of success.